Discourse Traditions in Liviu Rebreanu’s Novels Ion and Răscoala - Voicu-Stanciu, Mihaela (Acta Universitatis Danubius. Communicatio, 2024)
In this article, we aim at proving that a certain discourse tradition, regarding the usage of expressive phraseologisms in prose, does not function properly when it comes to Liviu Rebreanu’s two novels, namely Ion and Răscoala. Usually, as Cristinel Munteanu previously demonstrated, in the literary texts authored by writers such as Duiliu Zamfirescu, Mihail Sadoveanu, Fănuș Neagu etc., as a rule, one can identify the most expressive idioms and set phrases at the dialogued level, and not at the narrative level. It seems that in Liviu Rebreanu’s case this discourse tradition functions the other way round. Our study, based on a comprehensive analysis of both aforementioned novels, will confirm such a hypothesis.